Предмет: Алгебра,
автор: Аноним
Разложите на множители
(x-3)(3+x)-(x-3)^2
Срочно, пожалуйста!
Подробно.
Ответы
Автор ответа:
1
Ответ:
(x-3)(3+x)-(x-3)^2 = (x^2 - 9) - (x^2 - 6x + 9) = x^2 - 9 - x^2 + 6x - 9 = 6x - 18 = 6(x-3)
Ответ: 6(x-3)
Автор ответа:
0
Ответ:Ответ: 6(x-3).
Объяснение:Ответ: (x-3)(3+x)-(x-3)^2 = (x^2 - 9) - (x^2 - 6x + 9) = x^2 - 9 - x^2 + 6x - 9 = 6x - 18 = 6(x-3). Ответ: 6(x-3).
Похожие вопросы
Предмет: Математика,
автор: Mefedron1
Предмет: История,
автор: snitkovskaana
Предмет: Биология,
автор: sapacinskijrenat
Предмет: Физика,
автор: raaay1212
Предмет: Английский язык,
автор: MrokosPL58